Background, problems and solutions for introducing Islamic insurance in the United Kingdom - A. N. Zhilkina; M.-H. R. Orusbiev (Вестник университета)
The article is devoted to the study of Islamic insurance in the United Kingdom. It has been established that insurance is a major component of the state’s financial system. At the same time, there has been a rapid development of Islamic finance in recent years. The total Muslim population in the UK in 2020 is 4,130,000. Despite its low Muslim population, Great Britain is taking a proactive stance in developing Islamic finance. Despite the low number of Muslims, Great Britain is taking an active position in the development of Islamic finance. The country has established principles for the development of takafuls, and the market is being regulated. In addition, an ambitious target has been set for London to become an Islamic finance centre. There are currently positive trends in the takaful market. Despite this situation, further development in this area is required.